Application of taurine potassium in perovskite solar cell and preparation method
By using potassium taurate as a buried base modification material in perovskite solar cells, the problems of carrier recombination and stability of the perovskite battery interface are solved, and the effect of improving the photoelectric conversion efficiency and stability is achieved, and the battery is enhanced comprehensive performance.
Patent Information
- Application Number
- CN202411228449.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-20
AI Technical Summary
Existing perovskite solar cells have shortcomings in improving photoelectric conversion efficiency and stability, especially in terms of challenges in interfacial carrier recombination, energy level barrier, surface roughness and ion migration, which leads to insufficient competitiveness in their industries. .
Potassium taurate is used as the buried base modification material, and the interface modification layer is formed between the electron transport layer and the perovskite absorbing layer or hole transport layer, and its bipolar molecules are used to form a perovskite and metal oxides. dipole-dipole interactions improve the chemical stability of the material and release residual stresses at the interface.
Effectively inhibit the migration of halogen ions, prevent metal oxide corrosion, improve the photoelectric conversion efficiency and comprehensive performance of perovskite batteries, and significantly improve the stability and performance of the battery.
Smart Images

Figure CN119173060A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite photovoltaics, and in particular relates to an application of potassium taurine in a perovskite solar cell and a preparation method thereof. Background Art
[0002] As a new generation of photovoltaic clean energy technology, perovskite solar cells have received widespread attention from academia and industry. The "Plan for Scientific and Technological Innovation in the Energy Field" issued by the National Energy Administration lists solar power generation and utilization technology as a key task, including sub-tasks such as high-efficiency perovskite battery preparation and industrial production technology and high-efficiency and low-cost photovoltaic battery technology. As of now, the certified efficiency of perovskite cells has exceeded 26%, which is close to the highest efficiency of monocrystalline silicon solar cells. With the continuous cost reduction and efficiency improvement of silicon cells, perovskite cells urgently need to optimize the preparation process to improve industrial competitiveness.
[0003] Bottom modification is an effective method to improve the photoelectric conversion efficiency of batteries. The buried modification method of formal perovskite batteries generally introduces buried modification materials at the interface between the electron transport layer and the perovskite light absorbing layer. The buried modification method of trans perovskite batteries generally introduces buried modification materials at the interface between the hole transport layer and the perovskite light absorbing layer. The application of buried materials can improve the photoelectric conversion efficiency and stability of perovskite batteries through microscopic mechanisms such as inhibiting interface carrier recombination, slowing down interface energy level barriers, reducing surface roughness, releasing interface residual stress, inhibiting interface ion migration, reducing perovskite crystallization reaction enthalpy, and passivating interface defects. Finding stable and effective buried materials is the key to the buried modification method. Summary of the invention
[0004] In view of the shortcomings of the prior art, the primary purpose of the present invention is to provide an application and preparation method based on potassium taurine in perovskite solar cells. By burying the organic salt material in the present invention into the electron transport layer / perovskite light absorbing layer interface or the hole transport layer / perovskite light absorbing layer interface, the photoelectric conversion efficiency of the perovskite solar cell can be improved.
[0005] The first object of the present invention is to provide an application of potassium taurine in a perovskite solar cell, wherein the application is specifically to use potassium taurine to form a buried interface modification layer at the interface between an electron transport layer and a perovskite light absorbing layer; the chemical formula of the potassium taurine is:
[0006] The second object of the present invention is to provide a perovskite solar cell, wherein the perovskite solar cell comprises a buried interface modification layer formed at the interface between the potassium taurine-modified electron transport layer and the perovskite light absorbing layer.
[0007] The third object of the present invention is to provide a perovskite solar cell prepared by a bottom modification method and its performance parameters.
[0008] Specifically, the perovskite solar cell is composed of a conductive glass substrate, an electron transport layer, a buried modification layer, a perovskite light absorption layer, a hole transport layer and a metal back electrode stacked from bottom to top.
[0009] Specifically, the electron transport layer includes any one of tin dioxide, titanium dioxide, zinc oxide, tungsten oxide, molybdenum oxide, or a composite thereof.
[0010] Specifically, the perovskite light-absorbing layer includes but is not limited to any one of methylamine lead iodine (MAPbI3), formamidine lead iodine (FAPbI3), methylamine lead bromide (MAPbBr3), formamidine lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3), methylamine tin bromide (MASnBr3) and their composites.
[0011] Specifically, the hole transport layer includes, but is not limited to, any one of poly 3-hexylthiophene (P3HT) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD).
[0012] The preparation method technical scheme adopted by the present invention is as follows:
[0013] A method for preparing a perovskite solar cell, the method comprising the following steps:
[0014] (1) ultrasonically cleaning a conductive glass substrate in deionized water, acetone and ethanol solutions in sequence, drying with nitrogen, and treating in an ultraviolet ozone cleaning machine for 10-30 minutes, and forming a carrier transport layer on the surface of the substrate by coating or evaporation;
[0015] (2) dissolving equimolar amounts of taurine and potassium hydroxide solid in water to obtain a potassium taurate aqueous solution with a concentration of 0.2-10 mg / ml, and spin coating the solution on the substrate at a speed of 2000-5000 r / min for 20-60 s;
[0016] (3) Assemble the perovskite light absorption layer, carrier transport layer and back electrode in sequence on the substrate surface.
[0017] Specifically, the potassium taurine in step (2) can be replaced by any one or more of sodium taurine, zinc taurine, sodium homotaurine, potassium homotaurine, zinc homotaurine, potassium p-aminobenzenesulfonate, sodium p-aminobenzenesulfonate, zinc p-aminobenzenesulfonate and other soluble taurine, homotaurine and p-aminobenzenesulfonate.
[0018] Specifically, the aqueous solution in step (2) can be replaced by a mixed solution consisting of any one or more polar solvents of ethanol solution, isopropanol solution or n-butanol solution and water.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The buried modification material molecules used in the present invention have strong bipolarity, and the positive and negative charge centers of the molecules can respectively undergo dipole-dipole interactions with the perovskite molecules and the metal oxide molecules in the transport layer, thereby improving the chemical stability of the perovskite material, inhibiting the migration of halogen ions, preventing the metal oxide from being corroded by halogens, and to a certain extent utilizing the flexibility of the organic molecules to release the residual stress at the interface of the electron transport layer / perovskite light absorbing layer, thereby ultimately improving the comprehensive performance of the perovskite battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The structural diagram of the formal perovskite battery prepared by the present invention;
[0022] Figure 2 A structural diagram of an inverse perovskite battery prepared by the present invention;
[0023] Figure 3 This is a statistical chart of the photoelectric conversion efficiency of the perovskite cells prepared in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0024] Here, exemplary embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application.
[0025] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0026] If the specific conditions are not specified in the embodiments of the present invention, the conditions are carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or obtained commercially. The technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians of the art without making creative work are within the scope of protection of the present invention.
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] It should be noted that, in the absence of conflict, the features in the following embodiments and implementations may be combined with each other.
[0029] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0030] An application of potassium taurine in perovskite solar cells, wherein the application is to use potassium taurine to form a buried interface modification layer at the interface between an electron transport layer and a perovskite light absorbing layer; the chemical formula of the potassium taurine is:
[0031]
[0032] The perovskite solar cell is composed of a conductive glass substrate, an electron transport layer, a buried modification layer, a perovskite light absorption layer, a hole transport layer and a metal back electrode stacked from bottom to top.
[0033] The electron transport layer includes any one of tin dioxide, titanium dioxide, zinc oxide, tungsten oxide, molybdenum oxide or any one of their composites.
[0034] The perovskite light-absorbing layer includes but is not limited to any one of methylamine lead iodine (MAPbI3), formamidine lead iodine (FAPbI3), methylamine lead bromide (MAPbBr3), formamidine lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3), methylamine tin bromide (MASnBr3) and their composites.
[0035] The hole transport layer includes but is not limited to any one of poly 3-hexylthiophene (P3HT) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD). The hole transport layer and the electron transport layer can be collectively referred to as a carrier transport layer, and the SAM layer is an electron blocking layer and can also be used as a carrier transport layer.
[0036] Example 1
[0037] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 15 minutes. The SnO2 nanocolloid solution was spin-coated on the surface of the ITO glass and annealed on a 150°C hot plate for 1 hour to obtain a SnO2 electron transport layer. Equimolar amounts of taurine and potassium hydroxide solids were dissolved in water to obtain a potassium taurine aqueous solution with a concentration of 0.5 mg / ml. 50 μl of the potassium taurine aqueous solution was taken and spin-coated on the substrate surface at a speed of 3500 r / min for 30 seconds to obtain a buried bottom modification layer. Then, an equal amount of MAI and PbI2 was dissolved in DMSO to form a solution with a concentration of 1 mol / L, and the solution was spin-coated on the substrate surface. The speed of the coating machine was set to 3000 r / min. After drying for 25 seconds, 50 μl of chlorobenzene was dropped on the center of the perovskite substrate. After spin coating at 3000 r / min for 10 seconds, the ITO glass was placed on a 160°C hot plate and heated for 10 minutes to obtain a perovskite light-absorbing layer. The chlorobenzene solution of Spiro-OMeTAD, an acetonitrile solution with 4-tert-butylpyridine (tBP) and Li-TFSI, was spin-coated on the perovskite substrate as a hole transport layer. Finally, the substrate was placed in an evaporator and an 80 nm gold film was evaporated as the back electrode, such as Figure 1 shown.
[0038] The potassium taurine can be replaced by any one or more of sodium taurine, zinc taurine, sodium homotaurine, potassium homotaurine, zinc homotaurine, potassium p-aminobenzenesulfonate, sodium p-aminobenzenesulfonate, zinc p-aminobenzenesulfonate and other soluble taurine salts, homotaurine salts and p-aminobenzenesulfonate salts.
[0039] The aqueous solution can be replaced by a mixed solution consisting of any one or more polar solvents of ethanol solution, isopropanol solution or n-butanol solution and water.
[0040] Example 2
[0041] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 20 minutes. The aqueous solution containing Sn salt colloid was spin-coated on the surface of the ITO glass and annealed on a 180°C hot stage for 30 minutes to obtain a SnO2 electron transport layer. Equimolar amounts of taurine and sodium hydroxide solids were dissolved in a mixed solvent of ethanol and water (the volume ratio of ethanol to water was 1:3) to obtain a sodium taurine solution with a concentration of 0.8 mg / ml. 50 μl of the sodium taurine solution was taken and spin-coated on the substrate surface at a speed of 4000 r / min for 25 seconds to obtain a buried bottom modification layer. Equimolar amounts of FAI and PbI2 were dissolved in DMSO to form a solution with a concentration of 1.5 mol / L, which was spin-coated on the substrate surface. Set the speed of the glue machine to 3000r / min, spin dry for 15 seconds, drop 80μL of chlorobenzene on the center of the perovskite substrate, spin coat at 3000r / min for 30 seconds, and heat the ITO glass on a 130℃ hot plate for 10 minutes to obtain a perovskite light-absorbing layer. Add 4-tert-butylpyridine (tBP) and Li-TFSI to the acetonitrile solution of Spiro-OMeTAD and spin coat it on the perovskite substrate as a hole transport layer. Finally, place the substrate in an evaporator and evaporate a 70nm gold film as the back electrode.
[0042] Example 3
[0043] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 20 minutes. The SnO2 nanocolloid solution was spin-coated on the surface of the ITO glass and then annealed on a 150°C hot stage for 40 minutes to obtain a SnO2 electron transport layer. Equimolar amounts of high taurine and sodium hydroxide were dissolved in water to prepare a sodium high taurine aqueous solution with a concentration of 1 mg / ml. 60 μl of the sodium high taurine aqueous solution was taken and spin-coated on the substrate surface at a speed of 3500 r / min for 25 seconds to obtain a buried bottom modification layer. MAPbI3 was dissolved in cyclopentane sulfone to form a uniform solution with a concentration of 1.25 mol / L, and it was spin-coated on the substrate surface. The speed of the gelator was set to 3000 r / min. After drying for 30 seconds, 80 μl of ethyl acetate was dropped on the center of the perovskite substrate. After spin-coating at 3500 r / min for 20 seconds, the ITO glass was placed on a 110°C hot stage and heated for 15 minutes. The chlorobenzene solution of Spiro-OMeTAD in acetonitrile solution with 4-tert-butylpyridine (tBP) and Li-TFSI was spin-coated on the perovskite substrate as a hole transport layer. Finally, the substrate was placed in a magnetron sputtering instrument and a 80nm silver film was vacuum sputtered as the back electrode.
[0044] Example 4
[0045] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 20 minutes. The aqueous solution containing Zn salt colloid was spin-coated on the surface of the ITO glass and annealed on a 160°C hot stage for 1 hour to obtain a SnO2 electron transport layer. Para-aminobenzenesulfonic acid and zinc oxide (molar ratio of 2:1) were dissolved in water to prepare a 1mg / ml aqueous solution of zinc para-aminobenzenesulfonic acid. 60μl of the zinc para-aminobenzenesulfonic acid aqueous solution was taken and spin-coated on the substrate surface at a speed of 3500r / min for 25s to obtain a buried bottom modification layer. FAPbI3 was dissolved in a mixed solution of DMSO and DMF (DMSO and DMF volume ratio 5:1) to form a uniform solution with a concentration of 1.0mol / L, and it was spin-coated on the substrate surface. Set the speed of the glue machine to 3000r / min, spin dry for 30 seconds, drop 65μL of chlorobenzene solution on the center of the perovskite substrate, spin coat at 3500r / min for 20 seconds, and heat the ITO glass on a 140℃ hot plate for 15 minutes to obtain a perovskite light-absorbing layer. Add 4-tert-butylpyridine (tBP) and Li-TFSI acetonitrile solution Spiro-OMeTAD chlorobenzene solution and spin coat on the perovskite substrate as a hole transport layer. Finally, place the substrate in a magnetron sputtering instrument and vacuum sputter 80nm silver film as the back electrode.
[0046] Example 5
[0047] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 10 minutes. The aqueous solution containing Sn salt colloid was spin-coated on the surface of the ITO glass and then annealed on a 180°C hot stage for 1.5 hours to obtain a SnO2 electron transport layer. Taurine, potassium hydroxide and sodium hydroxide (molar ratio of 2:1:1) were dissolved in water to obtain a mixed aqueous solution of sodium taurine and potassium taurine with a concentration of 2 mg / ml (the molar ratio of sodium taurine to potassium taurine was 1:1). 70 μl of the mixed aqueous solution of sodium taurine and potassium taurine was taken and spin-coated on the substrate surface at a speed of 4500 r / min for 35 seconds to obtain a buried bottom modification layer. MAPbI3 and CsPbBr3 were dissolved in a mixed solvent of sulfolane and DMSO (the molar ratio of sulfolane to DMSO was 1:5) at a molar ratio of 19:1 to form a uniform solution with a total molar weight of 2.0 mol / L, and then spin-coated on the substrate surface. The speed of the gelling machine was set to 3000r / min. After drying for 15 seconds, 110μL of 0.6g / mL terephthaloyl chloride ethyl acetate solution was dropped on the center of the perovskite substrate. After spin coating at 3000r / min for 15 seconds, the ITO glass was placed on a 110℃ hot stage and heated for 10 minutes to obtain a perovskite light-absorbing layer. The chlorobenzene solution of Spiro-OMeTAD, an acetonitrile solution with 4-tert-butylpyridine (tBP) and Li-TFSI, was spin-coated on the perovskite substrate as a hole transport layer. Finally, the substrate was placed in a magnetron sputtering instrument, and an 80nm gold film was vacuum sputtered as the back electrode.
[0048] Example 6
[0049] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 20 minutes. The isopropanol solution containing Me-4PACz was spin-coated on the surface of the ITO glass and annealed on a 120°C hot plate for 20 minutes to obtain a SAM hole transport layer. Equimolar amounts of taurine and potassium hydroxide were dissolved in a mixed solution of ethanol and water (the volume ratio of ethanol to water was 1:4) to obtain a potassium taurine solution with a concentration of 1 mg / ml. 70 μl of the potassium taurine solution was taken and spin-coated on the substrate surface at a speed of 4500 r / min for 35 seconds to obtain a buried bottom modification layer. Dissolve FAPbI3 and CsPbBr3 in a mixed solvent of DMF and DMSO (the molar ratio of DMF to DMSO is 1:4) at a molar ratio of 15:1 to form a uniform solution with a total molar weight of 1.5 mol / L, and spin-coat it on the substrate surface. Set the speed of the gel coater to 3000 r / min. After drying for 25 seconds, drop 80 μL of chlorobenzene solution on the center of the perovskite substrate. After spinning at 3000 r / min for 15 seconds, place the ITO glass on a 110°C hot plate and heat for 10 minutes to obtain a perovskite light-absorbing layer. Spin-coat the chlorobenzene solution containing PC61BM on the perovskite substrate as an electron transport layer. Finally, place the substrate in a magnetron sputtering instrument and vacuum sputter a 100 nm silver film as the back electrode, such as Figure 2 shown.
[0050] Example 7
[0051] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen and treated in a UV ozone cleaning machine for 25 minutes. A mixed solution of water and isopropanol (the molar ratio of water to isopropanol is 4:1) containing polynickel oxide was spin-coated on the surface of the ITO glass and annealed on a hot plate at 180°C for 30 minutes to obtain a hole transport layer. Equimolar amounts of high taurine and sodium hydroxide were dissolved in water to prepare a sodium high taurine aqueous solution with a concentration of 1.5 mg / ml. 60 μl of the sodium high taurine aqueous solution was taken and spin-coated on the substrate surface at a speed of 3500 r / min for 25 seconds to obtain a buried bottom modification layer. FAPbI3 and CsPbI3 were dissolved in a mixed solvent of DMF and DMSO (the molar ratio of DMF to DMSO was 1:4) at a molar ratio of 12:1 to form a uniform solution with a total molar amount of 2.0 mol / L. Then spin coat it on the substrate surface, set the speed of the coating machine to 4000r / min, spin dry for 25 seconds, drop 120μL of chlorobenzene solution on the center of the perovskite substrate, spin coat at 4000r / min for 15 seconds, and heat the ITO glass on a 150℃ hot plate for 10 minutes to obtain a perovskite light absorption layer. Spin coat the chlorobenzene solution containing PC61BM on the perovskite substrate as an electron transport layer. Finally, place the substrate in a magnetron sputtering instrument and vacuum sputter 80nm silver film as the back electrode.
[0052] Comparative Example 1 (without bottom modification layer)
[0053] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solution in sequence, dried with nitrogen, and treated in a UV ozone cleaning machine for 15 minutes. The SnO2 nanocolloid solution was spin-coated on the ITO glass surface and annealed on a 150℃ hot stage for 1 hour to obtain the SnO2 electron transport layer. Then, equimolar amounts of MAI and PbI2 were dissolved in DMSO to form a solution with a concentration of 1 mol / L, and it was spin-coated on the substrate surface. The speed of the gelling machine was set to 3000r / min. After drying for 25 seconds, 50μl of chlorobenzene was dropped on the center of the perovskite substrate. After spin coating at 3000r / min for 10 seconds, the ITO glass was placed on a 160℃ hot stage and heated for 10 minutes to obtain the perovskite light absorption layer. The chlorobenzene solution of Spiro-OMeTAD, an acetonitrile solution with 4-tert-butylpyridine (tBP) and Li-TFSI, was spin-coated on the perovskite substrate as a hole transport layer. Finally, the substrate was placed in an evaporator and an 80nm gold film was evaporated as the back electrode.
[0054] Depend on Figure 3 It can be seen that the efficiency of the cells prepared in Examples 1-3 is significantly higher than that in Comparative Example 1. Therefore, the use of the bottom-burying modification method described in the present invention to prepare perovskite cells can improve the photoelectric conversion efficiency of the cells.
[0055] Those skilled in the art will readily appreciate other embodiments of the present application after considering the specification and practicing the contents disclosed herein. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or customary technical means in the art that are not disclosed in the present application.
[0056] It should be understood that the present application is not limited to the exact construction that has been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof.
Claims
1. An application of potassium taurine in perovskite solar cells, characterized in that: The application is specifically to use potassium taurine to form a buried interface modification layer at the interface between the electron transport layer and the perovskite light absorption layer; the structural formula of potassium taurine is:
2. A perovskite solar cell, characterized in that: The perovskite solar cell comprises a buried interface modification layer formed at the interface between the potassium taurine modified electron transport layer according to claim 1 and the perovskite light absorbing layer.
3. The perovskite solar cell according to claim 2, characterized in that: The perovskite solar cell is composed of a conductive glass substrate, an electron transport layer, a buried modification layer, a perovskite light absorption layer, a hole transport layer and a metal back electrode stacked from bottom to top.
4. The perovskite solar cell according to claim 2, characterized in that: The electron transport layer includes any one of tin dioxide, titanium dioxide, zinc oxide, tungsten oxide, molybdenum oxide or a composite thereof.
5. The perovskite solar cell according to claim 2, characterized in that: The perovskite light-absorbing layer includes but is not limited to any one of methylamine lead iodine (MAPbI3), formamidine lead iodine (FAPbI3), methylamine lead bromide (MAPbBr3), formamidine lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3), methylamine tin bromide (MASnBr3) and their composites.
6. The perovskite solar cell according to claim 2, characterized in that: The hole transport layer includes, but is not limited to, any one of poly 3-hexylthiophene (P3HT) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD).
7. A method for preparing a perovskite solar cell according to any one of claims 2 to 6, characterized in that: The preparation method comprises the following steps: (1) ultrasonically cleaning a conductive glass substrate in deionized water, acetone and ethanol solutions in sequence, drying with nitrogen, and treating in an ultraviolet ozone cleaning machine for 10-30 minutes, and forming a carrier transport layer on the surface of the substrate by coating or evaporation; (2) dissolving equimolar amounts of taurine and potassium hydroxide solid in water to obtain a potassium taurate aqueous solution with a concentration of 0.2-10 mg / ml, and spin coating the solution on the substrate at a speed of 2000-5000 r / min for 20-60 s; (3) Assemble the perovskite light absorption layer, carrier transport layer and back electrode in sequence on the substrate surface.
8. The method for preparing a perovskite solar cell according to claim 7, characterized in that: The potassium taurine in the step (2) can be replaced by any one or more of sodium taurine, zinc taurine, sodium homotaurine, potassium homotaurine, zinc homotaurine, potassium p-aminobenzenesulfonate, sodium p-aminobenzenesulfonate, zinc p-aminobenzenesulfonate and other soluble taurine, homotaurine and p-aminobenzenesulfonate.
9. The method for preparing a perovskite solar cell according to claim 7, characterized in that: The aqueous solution in step (2) can be replaced by a mixed solution consisting of any one or more polar solvents of ethanol solution, isopropanol solution or n-butanol solution and water.
